Skip to main content

On the degenerate \((h,q)\)-Changhee numbers and polynomials

Abstract

The Changhee numbers and polynomials are introduced by Kim, Kim and Seo (Adv. Stud. Theor. Phys. 7(20):993–1003, 2013), and the generalizations of those polynomials are characterized. In this paper, we investigate a new q-analog of the higher order degenerate Changhee polynomials and numbers. We derive some new interesting identities related to the degenerate \((h,q)\)-Changhee polynomials and numbers.

Introduction

For a fixed odd prime number p, we make use of the following notation. \(\mathbb{Z}_{p}\), \(\mathbb{Q}_{p}\), and \(\mathbb{C}_{p}\) will denote the ring of p-adic rational integers, the field of p-adic rational numbers and the completions of algebraic closure of \(\mathbb {Q}_{p}\), respectively. The p-adic norm is defined \(|p|_{p} = p^{-1}\) (see [14, 15, 17, 19, 30]).

When one says q-extension, q is variously considered as an indeterminate, a complex \(q \in\mathbb{C}\), or p-adic number \(q \in \mathbb{C}_{p}\). If \(q \in\mathbb{C}\), one normally assumes that \(|q|<1\). If \(q \in\mathbb{C}_{p}\), then we assume that \(|q-1|_{p} < p^{-\frac{1}{p-1}}\) so that \(q^{x} = \exp(x\log q)\), \(|x|_{p}\leq1\).

The q-analog of number x is defined as

$$ [x]_{q} =\frac{1- q^{x}}{1-q}. $$

Note that \(\lim_{q \rightarrow1} [x]_{q} = x \) for each \(x \in\mathbb{Z}_{p}\).

Let \(UD(\mathbb{Z}_{p})= \{f|f:{\mathbb{Z}}_{p} \rightarrow{\mathbb {R}}\text{ is uniformly differentiable} \}\). For \(f\in UD({\mathbb{Z}_{p}})\), the fermionic p-adic q-integral on \({\mathbb{Z}_{p}}\) is defined by Kim as follows (see [9, 14, 15, 17, 19, 20]):

$$ I_{-q}(f)= \int_{\mathbb{Z}_{p}}f(x)\,d\mu_{-q}(x)=\lim_{N \rightarrow\infty} \frac{1}{[p^{N}]_{-q}}\sum_{x=0}^{p^{N}-1} f(x) (-q)^{x}. $$
(1)

If we put \(f_{1}\) to the translation of f with \(f_{1} (x )=f (x+1 )\), then, by (1), we get

$$ qI_{-q}(f_{1})+I_{-q} (f)=[2]_{q}f(0)\quad \text{(see [1, 17--20, 23, 24, 28, 31])}. $$
(2)

As is well known, the Stirling number of the first kind is defined by

$$ (x )_{n}=x (x-1 )\cdots (x-n+1 )=\sum _{l=0}^{n}S_{1} (n,l )x^{l}, $$
(3)

and the Stirling number of the second kind is given by the generating function to be

$$ \bigl(e^{t}-1 \bigr)^{m}=m!\sum _{l=m}^{\infty}S_{2} (l,m )\frac{t^{l}}{l!} \quad \text{(see [3--5, 11])}. $$
(4)

By (3), we have

$$ \bigl(\log(1+x) \bigr)^{n}=n!\sum _{l=n} ^{\infty}S_{1}(l,n)\frac {x^{l}}{l!} \quad (n\geq0). $$
(5)

The unsigned Stirling numbers of the first kind are given by

$$ x^{(n)}=x(x+1)\cdots(x+n-1)=\sum _{l=0} ^{n} \bigl\vert S_{1}(n,l) \bigr\vert x^{l}\quad \text{(see [3, 5])}. $$
(6)

Note that if we replace x to −x in (3), then

$$\begin{aligned} (-x)_{n}&=(-1)^{n}x^{(n)}=\sum _{l=0} ^{n} S_{1}(n,l) (-1)^{l}x^{l} \\ &=(-1)^{n}\sum_{l=0} ^{n} \bigl\vert S_{1}(n,l) \bigr\vert x^{l} \end{aligned}$$
(7)

(see [3, 5, 28, 31]). Hence \(S_{1}(n,l)=|S_{1}(n,l)|(-1)^{n-l}\).

In [16], Kim firstly constructed the new \((h,q)\)-extension of the Bernoulli numbers and polynomials with the aid of q-Volkenborn integration, and Simsek gave the Witt-formula for \((h,q)\)-Bernoulli numbers in [27, 34]. Ozden and Simsek defined \((h,q)\)-extension of Euler numbers and polynomials withe the aid of fermionic integral of the function \(f(x)=q^{hx}e^{xt}\) in [29], and found recurrence identities for \((h,q)\)-Euler polynomials and the alternating sums of powers of consecutive \((h,q)\)-integers in [35]. In Chapter 6 of [27], the author discusses several generalizations of Bernoulli numbers and associated polynomials with interpolation at negative integers.

Kim et al. introduced the Changhee polynomials of the first kind of order r, defined by the generating function to be

$$ \biggl(\frac{2}{2+t} \biggr)^{r}(1+t)^{x}= \sum_{n=0} ^{\infty}\operatorname{Ch}_{n} ^{(r)}(x) \frac{t^{n}}{n!} \quad \text{(see [12, 13])}, $$
(8)

and Moon et al. defined the q-Changhee polynomials of order r as follows:

$$ \biggl(\frac{1+q}{q(1+t)+1} \biggr)^{r}(1+t)^{x}=\sum _{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(r)}(x)\frac{t^{n}}{n!}\quad \text{(see [28, 31])}. $$

By (2), we note that

$$ \biggl(\frac{1+q}{q(1+t)+1} \biggr)^{r}(1+t)^{x}={ \int_{\mathbb {Z}_{p}}}(1+t)^{x+y}\,d\mu_{-q}(y), $$

and thus we see that \(\sum_{n=0} ^{\infty}\operatorname{Ch}_{n} ^{(r)}(x) \frac {t^{n}}{n!}={\int_{\mathbb{Z}_{p}}}(1+t)^{x+y}\,d\mu_{-q}(y)\).

In [31], the authors defined the generalization of the q-Changhee polynomials which are called by \((h,q)\)-Changhee polynomials of the first kind and \((h,q)\)-Changhee polynomials of the second kind, respectively, defined by the fermionic p-adic q-integral on \({\mathbb{Z}}_{p}\) to be

$$\begin{aligned}& \begin{aligned}[b] \sum_{n=0} ^{\infty}\operatorname{Ch}_{n,h,q} (x)\frac{t^{n}}{n!}&={ \int_{\mathbb {Z}_{p}}}q^{h}y(1+t)^{x+y}\,d \mu_{-q}(y) \\ &=\frac{1+q}{q^{h+1}(1+t)+1}(1+t)^{x}, \end{aligned} \end{aligned}$$
(9)
$$\begin{aligned}& \begin{aligned}[b] \sum_{n=0} ^{\infty}{\widehat{\operatorname{Ch}}}_{n,h,q} (x) \frac{t^{n}}{n!}&={ \int _{\mathbb{Z}_{p}}}q^{hy}(1+t)^{-x-y}\,d \mu_{-q}(y) \\ &=\frac{1+q}{q^{h+1}+1+t}(1+t)^{r-x}. \end{aligned} \end{aligned}$$
(10)

As is well known, the Euler polynomials are defined by the generating function to be

$$ \frac{2}{e^{t}+1}e^{xt}=\sum_{n=0} ^{\infty} E_{n}(x)\frac {t^{n}}{n!}\quad \text{(see [2, 7, 8, 17, 19, 20, 33, 36, 37])}. $$

In [4], Carlitz first introduced the concept of degenerate numbers and polynomials which are related to Euler polynomials as follows:

$$ \sum_{n=0} ^{\infty}E_{n} (x|\lambda) \frac{t^{n}}{n!}=\frac {2}{(1+\lambda t)^{\frac{1}{\lambda}}+1}(1+\lambda t)^{\frac {x}{\lambda}}, $$
(11)

where \(\lambda\in{\mathbb{R}}\). Note that, by (11), we see that

$$\begin{aligned} \lim_{\lambda\rightarrow0}\sum_{n=0} ^{\infty}E_{n} (x|\lambda )\frac{t^{n}}{n!}&=\lim _{\lambda\rightarrow0}\frac{2}{(1+\lambda t)^{\frac{1}{\lambda}}+1}(1+\lambda t)^{\frac{x}{\lambda}} \\ &=\frac{2}{e^{t}+1}e^{xt}=\sum_{n=0} ^{\infty}E_{n} (x)\frac{t^{n}}{n!}, \end{aligned}$$

and thus we get

$$ \lim_{\lambda\rightarrow0}E_{n} (x|\lambda)=E_{n}(x). $$

In the recent years, the degenerate of some special polynomials are investigated by many authors (see [4, 10, 11, 21,22,23,24, 26]). In particular, the degenerate Changhee polynomials which are defined by the generating function to be

$$ \sum_{n=0} ^{\infty} \operatorname{Ch}_{n,\lambda} ^{*} (x)\frac{t^{n}}{n!}= \frac {2\lambda}{2\lambda+\log(1+\lambda t)} \bigl(1+\log(1+\lambda )^{\frac{1}{\lambda t}} \bigr)^{x} \quad \text{(see [26])}, $$
(12)

and Kim et al. defined the degenerate q-Changhee polynomials as follows:

$$ \sum_{n=0} ^{\infty} \operatorname{Ch}_{n,\lambda,q}(x) \frac{t^{n}}{n!}=\frac {q\lambda+\lambda}{q\log(1+\lambda t)+q\lambda+\lambda} \bigl(1+\log(1+\lambda t)^{\frac{1}{\lambda}} \bigr)^{x}\quad \text{(see [22, 24])}. $$
(13)

In the past decade, many researchers have investigated the various generalization of Changhee polynomials (see [1, 6, 12, 13, 24,25,26, 28, 31]), and in [1, 31], the authors gave new q-analog of Changhee numbers and polynomials.

In this paper, we introduce a new q-analog of degenerate Changhee numbers and polynomials of the first kind and the second kind of order r, and derive some new interesting identities related to the degenerate q-Changhee polynomials of order r.

q-Analog of degenerate Changhee polynomials

Let assume that \(\lambda,t \in{\mathbb{C}_{p}}\) with \(|\lambda t|< p^{-\frac{1}{p-1}}\). By (2), we get

$$\begin{aligned}& { \int_{\mathbb{Z}_{p}}}q^{hy} \biggl(1+\frac{1}{\lambda}\log (1+ \lambda t) \biggr)^{x+y}\,d\mu_{-q}(y) \\& \quad =\frac{1+q}{q^{h+1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \biggl(1+\frac {1}{\lambda}\log(1+\lambda t) \biggr)^{x}, \end{aligned}$$
(14)

where \(h\in{\mathbb{Z}}\). By (14), we define the q-analog of degenerate Changhee polynomials by the generating function to be

$$ \sum_{n=0} ^{\infty} \operatorname{Ch} _{n,h,q}(x|\lambda)\frac{t^{n}}{n!}=\frac {1+q}{q^{h+1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{x}. $$
(15)

In the special case \(x=0\), \(\operatorname{Ch}_{n,h,q} (\lambda)=\operatorname{Ch}_{n,h,q} (0|\lambda )\) are called the q-analog of degenerate Changhee numbers.

Note that

$$\begin{aligned} \lim_{\lambda\rightarrow0} \sum_{n=0} ^{\infty}\operatorname{Ch} _{n,h,q}(x|\lambda)\frac{t^{n}}{n!} &= \lim_{\lambda\rightarrow0} \frac{1+q}{q^{h+1} (1+\frac {1}{\lambda}\log(1+\lambda t) )+1} \biggl(1+\frac{1}{\lambda } \log(1+\lambda t) \biggr)^{x} \\ &=\frac{q+1}{q^{h+1}(1+t)+1}(1+t)^{x}=\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,h,q} (x)\frac{t^{n}}{n!}, \end{aligned}$$

and so we see that

$$ \lim_{\lambda\rightarrow0} \operatorname{Ch}_{n,h,q} (x|\lambda)=\operatorname{Ch}_{n,h,q} (x), $$
(16)

and, if we put \(h=0\), then

$$ \lim_{\lambda\rightarrow0}\operatorname{Ch}_{n,q} ^{(0)}(x|\lambda )=\operatorname{Ch}_{n,q}(x)\quad \text{and} \quad \operatorname{Ch}_{n,0,q}(x|\lambda)=\operatorname{Ch}_{n,\lambda,q}(x). $$
(17)

By (16) and (17), we see that q-analog of degenerate Changhee polynomials are closely related to the q-Changhee polynomials and degenerate q-Changhee polynomials.

By using (7) and (14), we have

$$\begin{aligned}& { \int_{\mathbb{Z}_{p}}}q^{hy} \biggl(1+\frac{1}{\lambda}\log (1+ \lambda t) \biggr)^{x+y}\,d\mu_{-q}(y) \\& \quad = { \int_{\mathbb{Z}_{p}}}q^{hy} \sum_{n=0} ^{\infty}\binom {x+y}{n}\lambda^{-n} \bigl(\log(1+\lambda t) \bigr)^{n}\,d\mu_{-q}(y) \\& \quad = { \int_{\mathbb{Z}_{p}}}q^{hy}\sum_{n=0} ^{\infty}\binom {x+y}{n}\lambda^{-n}n!\sum _{l=n} ^{\infty}S_{1}(l,n)\frac{(\lambda t)^{l}}{l!} \,d\mu_{-q}(y) \\& \quad = \sum_{n=0} ^{\infty}\sum _{m=0} ^{n} \lambda^{n-m}m!S_{1}(n,m){ \int _{\mathbb{Z}_{p}}}q^{hy}\binom{x+y}{m}\,d \mu_{-q}(y)\frac{t^{n}}{n!} \\& \quad = \sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n} \lambda ^{n-m}S_{1}(n,m){ \int_{\mathbb{Z}_{p}}}q^{hy} (x+y)_{m}\,d\mu _{-q}(y) \Biggr)\frac{t^{n}}{n!}. \end{aligned}$$
(18)

By (14) and (18), we have

$$ \operatorname{Ch}_{n,h,q} (x|\lambda)=\sum _{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int _{\mathbb{Z}_{p}}}q^{hy} (x+y)_{m}\,d \mu_{-q}(y). $$
(19)

By (3), we get

$$\begin{aligned} { \int_{\mathbb{Z}_{p}}}q^{hy} (x+y)_{m}\,d \mu_{-q}(y) &=\sum_{l=0} ^{m} S_{1}(m,l) { \int_{\mathbb{Z}_{p}}}q^{hy} (x+y)^{l} \,d\mu _{-q}(y) \\ &=\sum_{l=0} ^{m} S_{1}(m,l)E_{l} (x|h,q), \end{aligned}$$
(20)

where \(E_{n} (x|h,q)\) is the nth \((h,q)\)-Euler polynomials which are defined by the generating function to be

$$\begin{aligned} \sum_{n=0} ^{\infty} E_{n} (x|h,q) \frac{t^{n}}{n!}&={ \int_{\mathbb {Z}_{p}}}q^{hy}e^{t(x+y)}\,d \mu_{-q}(y) \\ &=\sum_{n=0} ^{\infty} \biggl({ \int_{\mathbb {Z}_{p}}}q^{hy}(x+y)^{n}\,d \mu_{-q}(y) \biggr)\frac{t^{n}}{n!} \\ &=\frac{q+1}{q^{h+1}e^{t}+1}e^{xt}\quad \text{(see [32])}. \end{aligned}$$

In addition,

$$\begin{aligned}& \frac{q+1}{q^{h+1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \\& \quad = (q+1)\sum_{m=0} ^{\infty}(-1)^{m}q^{m(h+1)} \biggl(1+\frac{1}{\lambda }\log(1+\lambda t) \biggr)^{m} \\& \quad = (q+1)\sum_{m=0} ^{\infty}(1-)^{m}q^{m(h+1)} \sum_{l=0} ^{m} \lambda ^{-l} \binom{m}{l} \bigl(\log(1+\lambda t) \bigr)^{l} \\& \quad = (q+1)\sum_{m=0} ^{\infty}q^{m(h+1)}(-1)^{m} \sum_{l=0} ^{m}\lambda ^{-l} \binom{m}{l}l!\sum_{r=l} ^{\infty}S_{1}(r,l) \lambda^{r}\frac {t^{r}}{r!} \\& \quad = (q+1)\sum_{n=0} ^{\infty}\sum _{l=0} ^{\infty }q^{(n+l)(h+1)}(-1)^{n+l} \binom{n+l}{l}\sum_{r=0} ^{\infty}\lambda ^{r} S_{1}(r+l,l)\frac{t^{r+l}}{(r+l)!} \\& \quad = \sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{\infty}\sum _{l=0} ^{n}q^{(m+l)(h+1)}(-1)^{m+l} \binom{m+l}{l}\lambda^{n-l}S_{1}(n,l) \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$
(21)

By (19), (20) and (21), we obtain the following theorem.

Theorem 2.1

For each nonnegative integer n, we have

$$\begin{aligned} \operatorname{Ch}_{n,h,q} (x|\lambda)&= \sum _{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int _{\mathbb{Z}_{p}}}q^{hy} (x+y)_{m}\,d \mu_{-q}(y) \\ &=\sum_{m=0} ^{n} \sum _{l=0} ^{m}\lambda^{n-m}S_{1}(n,m)S_{1}(m,l)E_{l} (x|h,q) \end{aligned}$$

and

$$ \operatorname{Ch}_{n,h,q} (\lambda)=\sum_{m=0} ^{\infty}\sum_{l=0} ^{n}q^{(m+l)(h+1)}(-1)^{m+l} \binom{m+l}{l}\lambda^{n-l}S_{1}(n,l). $$

By replacing t by \(\frac{1}{\lambda} (e^{\lambda t}-1 )\) in (15) and by using (4), we have

$$\begin{aligned} \frac{q+1}{q^{h+1}(1+t)+1}(1+t)^{x}&=\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(h)} (x|\lambda) \frac{1}{n!} \biggl(\frac{1}{\lambda} \bigl(e^{\lambda t}-1 \bigr) \biggr)^{n} \\ &=\sum_{n=0} ^{\infty}\operatorname{Ch}_{n,q} ^{(h)}(x|\lambda)\lambda^{-n}\frac {(e^{t}-1)^{n}}{\lambda} \\ &= \Biggl(\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(h)}(x|\lambda)\lambda ^{-n}\frac{1}{n!} \Biggr) \Biggl(n!\sum _{l=n} ^{\infty}S_{2}(l,n)\frac {(\lambda t)^{l}}{l!} \Biggr) \\ &=\sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n}\lambda^{n-m} \operatorname{Ch}_{m,q} ^{(h)}(x|\lambda)S_{2}(n,m) \Biggr)\frac{t^{n}}{n!}, \end{aligned}$$
(22)

and, thus, by (9) and (22), we have the following corollary.

Corollary 2.2

For each nonnegative integer n, we have

$$ \operatorname{Ch}_{n,h,q} (x)=\sum_{m=0} ^{n}\lambda^{n-m}S_{2}(n,m) \operatorname{Ch}_{m,h,q} (x|\lambda). $$

From (1) and (14), we note that

$$\begin{aligned}& \sum_{n=0} ^{\infty} \bigl(q^{h+1} \operatorname{Ch}_{n,h,q} (x+1|\lambda )+\operatorname{Ch}_{n,h,q} (x|\lambda) \bigr)\frac{t^{n}}{n!} \\& \quad = \frac{(q+1)}{q^{h+1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \biggl(q^{h+1} \biggl(1+\frac{1}{\lambda} \log(1+\lambda t) \biggr)+1 \biggr) \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{x} \\& \quad = (q+1) \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{x} \\& \quad = (q+1)\sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n} (x)_{m}\lambda ^{n-m}S_{1}(n,m) \Biggr)\frac{t^{n}}{n!}. \end{aligned}$$
(23)

By (23), we obtain the following theorem.

Theorem 2.3

For each nonnegative integer n, we get

$$ q^{h+1}\operatorname{Ch}_{n,h,q} (x+1|\lambda)+ \operatorname{Ch}_{n,h,q} (x|\lambda)=(q+1)\sum _{m=0} ^{n} (x)_{m}\lambda^{n-m}S_{1}(n,m). $$

For positive integer d with \(d\equiv1\ (\operatorname{mod} 2)\), if we put \(f(x)=q^{hx} (1+\frac{1}{\lambda}\log(1+\lambda t) )^{x}\), then, by (2) and (7), we have

$$\begin{aligned}& q^{d} { \int_{\mathbb{Z}_{p}}}q^{h(x+d)} \biggl(1+\frac{1}{\lambda }\log(1+ \lambda t) \biggr)^{x+d}\,d\mu_{-q}(x)+{ \int_{\mathbb {Z}_{p}}}q^{hx} \biggl(1+\frac{1}{\lambda}\log(1+ \lambda t) \biggr)^{x}\,d\mu_{-q}(x) \\& \quad = (q+1)\sum_{l=0} ^{d-1} (-1)^{l}q^{l(h+1)} \biggl(1+\frac{1}{\lambda }\log(1+\lambda t) \biggr)^{l} \\& \quad = (q+1)\sum_{l=0} ^{d-1}(-1)^{l}q^{l(h+1)} \sum_{k=0} ^{\infty}\binom {l}{k} \biggl( \frac{1}{\lambda}\log(1+\lambda t) \biggr)^{k} \\& \quad = (q+1)\sum_{l=0} ^{d-1}(-1)^{l}q^{l(h+1)} \sum_{k=0} ^{\infty}\binom {l}{k} \lambda^{-k}\sum_{r=k} ^{\infty}S_{1}(r,k) \frac{t^{r}}{r!} \\& \quad = \sum_{n=0} ^{\infty} \Biggl((q+1)\sum _{l=0} ^{d-1}\sum _{k=0} ^{n}(-1)^{l}q^{l(h+1)} \binom{l}{k}\lambda^{-k}S_{1}(n,k) \Biggr) \frac{t^{n}}{n!} \end{aligned}$$
(24)

and

$$\begin{aligned}& q^{d} { \int_{\mathbb{Z}_{p}}}q^{h(x+d)} \biggl(1+\frac{1}{\lambda }\log(1+ \lambda t) \biggr)^{x+d}\,d\mu_{-q}(x) \\& \qquad {}+{ \int_{\mathbb {Z}_{p}}}q^{hx} \biggl(1+\frac{1}{\lambda}\log(1+ \lambda t) \biggr)^{x}\,d\mu_{-q}(x) \\& \quad =\sum_{n=0} ^{\infty} \bigl(q^{d(h+1)} \operatorname{Ch}_{n,q} ^{(h)}(d|\lambda )+\operatorname{Ch}_{n,q} ^{(h)}(\lambda) \bigr) \frac{t^{n}}{n!}. \end{aligned}$$
(25)

By (24) and (25), we obtain the following theorem.

Theorem 2.4

For each nonnegative integer n and odd integer d, we have

$$ q^{d(h+1)} \operatorname{Ch}_{n,h,q} (d|\lambda)+ \operatorname{Ch}_{n,h,q} (\lambda)=(q+1)\sum _{l=0} ^{d-1}\sum_{k=0} ^{n}(-1)^{l}q^{l(h+1)}\binom{l}{k} \lambda^{-k}S_{1}(n,k). $$

q-Analog of higher order degenerate Changhee polynomials

In this section, we consider the q-analog of higher order degenerate Changhee polynomials which are defined by

$$\begin{aligned}& \operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) \\& \quad =\sum_{m=0} ^{n} \lambda^{n-m}S_{1}(n,m)\underbrace{{ \int_{\mathbb {Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}}_{r\text{-times}} q^{\sum_{i=1} ^{r}h_{i}y_{i}}(x+y_{1} \\& \qquad {}+ \cdots+y_{r})_{m}\,d\mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}), \end{aligned}$$
(26)

where n is a nonnegative integer, \(h_{1},\ldots,h_{r}\in{\mathbb{Z}}\) and \(r\in{\mathbb{N}}\).

By (26), we have

$$\begin{aligned}& \sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n}\lambda ^{n-m}S_{1}(n,m){ \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb {Z}_{p}}}q^{\sum_{i=1} ^{r}h_{i}y_{i}}(x+y_{1}+ \cdots+y_{r})_{m}\,d\mu _{-q}(y_{1}) \cdots \,d\mu_{-q}(y_{r}) \Biggr)\frac{t^{n}}{n!} \\& \quad = \sum_{n=0} ^{\infty} \sum _{m=0} ^{n} \lambda^{n-m}m!S_{1}(n,m){ \int _{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum_{i=1} ^{r} h_{i}y_{i}} \\& \qquad {}\times\binom{x+y_{1}+\cdots+y_{r}}{m}\,d \mu_{-q}(y_{1})\cdots \,d\mu _{-q}(y_{r}) \frac{t^{n}}{n!} \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}}\sum_{n=0} ^{\infty}\binom{x+y_{1}+\cdots +y_{r}}{n}\lambda^{-n}n! \\& \qquad {}\times\sum _{l=n} ^{\infty}S_{1}(l,n)\frac{(\lambda t)^{l}}{l!} \,d\mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}}\sum_{n=0} ^{\infty}\binom{x+y_{1}+\cdots +y_{r}}{n}\lambda^{-n} \bigl(\log(1+\lambda t) \bigr)^{n} \,d\mu _{-q}(y_{1})\cdots \,d \mu_{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}} \biggl(1+\frac{1}{\lambda}\log(1+ \lambda t) \biggr)^{x+y_{1}+\cdots+y_{r}}\,d\mu_{-q}(y_{1})\cdots \,d \mu_{-q}(y_{r}) \\& \quad = \prod_{i=1} ^{r} \biggl( \frac{1+q}{q^{h_{i}+1} (1+\frac{1}{\lambda }\log(1+\lambda t) )+1} \biggr) \biggl(1+\frac{1}{\lambda}\log (1+\lambda t) \biggr)^{x}. \end{aligned}$$
(27)

By (26) and (27), we see that

$$ \sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda)\frac{t^{n}}{n!}= \prod_{i=1} ^{r} \biggl(\frac{1+q}{q^{h_{i}+1} (1+\frac{1}{\lambda }\log(1+\lambda t) )+1} \biggr) \biggl(1+\frac{1}{\lambda}\log (1+\lambda t) \biggr)^{x}. $$
(28)

If we put

$$ F_{q} ^{(h_{1},\ldots,h_{r})}(x,t)=\prod_{i=1} ^{r} \biggl(\frac {1+q}{q^{h_{i}+1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \biggr) \biggl(1+\frac{1}{\lambda} \log(1+\lambda t) \biggr)^{x}, $$

then

$$\begin{aligned} F_{q} ^{(0,\ldots,0)}(x,t)&= \biggl(\frac{[2]_{q}}{[2]_{q}+\frac{q}{\lambda }\log(1+\lambda t)} \biggr)^{r} \biggl(1+\frac{1}{\lambda}\log (1+\lambda t) \biggr)^{x} \\ &=\sum_{n=0} ^{\infty}\operatorname{Ch}_{n,\lambda,q} ^{(r)}(x)\frac{t^{n}}{n!} \end{aligned}$$

and

$$\begin{aligned} \lim_{q\rightarrow1}F_{q} ^{(-1,\ldots,-1)}(x,t)&= \biggl( \frac {2}{\frac{1}{\lambda}\log(1+\lambda t)+2} \biggr)^{r} \biggl(1+\frac {1}{\lambda}\log(1+\lambda t) \biggr)^{x} \\ &=\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,\lambda} ^{(r)} (x)\frac{t^{n}}{n!}. \end{aligned}$$

Thus, \(F_{q} ^{(h_{1},\ldots,h_{r})}(x,t)\) seems to be a new q-extension of the generating function for the degenerate Changhee polynomials of order r.

Note that

$$\begin{aligned}& \prod_{i=1} ^{r} \biggl(\frac{1+q}{q^{h_{i}+1} (1+\frac{1}{\lambda }\log(1+\lambda t) )+1} \biggr) \biggl(1+\frac{1}{\lambda}\log (1+\lambda t) \biggr)^{x} \\& \quad = \Biggl(\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(\lambda )\frac{t^{n}}{n!} \Biggr) \Biggl(\sum_{n=0} ^{\infty}\sum _{m=0} ^{n} \binom{x}{m}\lambda^{n-m}m!S_{1}(n,m) \frac{t^{n}}{n!} \Biggr) \\& \quad = \sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n}\sum _{l=0} ^{n-m} \binom {x}{l}\binom{n}{m} \lambda^{n-m-l}l!\operatorname{Ch}_{m,q} ^{(h_{1},\ldots ,h_{r})}( \lambda)S_{1}(n-m,l) \Biggr)\frac{t^{n}}{n!}. \end{aligned}$$
(29)

Since

$$\begin{aligned}& (x+y_{1}+\cdots+y_{r})_{n} \\& \quad =\sum_{l=0} ^{n} S_{1}(n,l) (x+y_{1}+\cdots+y_{r})^{l} \\& \quad =\sum_{l=0} ^{n} S_{1}(n,l) \sum_{\substack{l_{1}+\cdots+l_{r}=l\\ l_{1},\ldots,l_{r}\geq0}} \binom{n}{l_{1},l_{2},\ldots,l_{r}}y_{1} ^{l_{1}}y_{2} ^{l_{2}} \cdots(x+y_{r}) ^{l_{r}}, \end{aligned}$$
(30)

where \(\binom{n}{l_{1},l_{2},\ldots,l_{r}}=\frac{n!}{l_{1}!l_{2}!\cdots l_{r}!}\), we have

$$\begin{aligned}& { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r}h_{i}y_{i}}(x+y_{1}+ \cdots+y_{r})_{m}\,d\mu_{-q}(y_{1})\cdots \,d\mu _{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r}h_{i}y_{i}}\sum_{l=0} ^{m} S_{1}(m,l) (x+y_{1}+\cdots+y_{r})^{l} \,d\mu _{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r}h_{i}y_{i}}\sum_{l=0} ^{m} S_{1}(m,l) \\& \qquad {}\times\sum_{\substack{l_{1}+\cdots +l_{r}=l\\l_{1},\ldots,l_{r}\geq0}} \binom{m}{l_{1},l_{2},\ldots,l_{r}}y_{1} ^{l_{1}}y_{2} ^{l_{2}} \cdots(x+y_{r}) ^{l_{r}} \,d\mu_{-q}(y_{1}) \cdots \,d\mu _{-q}(y_{r}) \\& \quad = \sum_{l=0} ^{m} S_{1}(m,l)\sum_{\substack{l_{1}+\cdots+l_{r}=l \\l_{1},\ldots,l_{r}\geq0}}\binom{m}{l_{1},l_{2},\ldots,l_{r}}E_{l_{1}} (h_{1},q)\cdots E_{l_{r-1}} (h_{r-1},q)E_{l_{r},q} (x|h_{r},q), \end{aligned}$$
(31)

where \(E_{n} (h,q)=E_{n} (0|h,q)\), which are called the \((h,q)\)-Euler numbers.

Thus, by (26) and (31), we obtain the following theorem.

Theorem 3.1

For \(n \geq0\), we have

$$\begin{aligned}& \operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) \\& \quad=\sum_{m=0} ^{n}\sum _{l=0} ^{m}\sum_{\substack{l_{1}+\cdots+l_{r}=l\\ l_{1},\ldots,l_{r}\geq0}} \lambda^{n-m}S_{1}(n,m) S_{1}(m,l) \binom {m}{l_{1},l_{2},\ldots,l_{r}} \\& \qquad {}\times E_{l_{1}} (h_{1},q)\cdots E_{l_{r-1}} (h_{r-1},q)E_{l_{r},q} (x|h_{r},q). \end{aligned}$$

By replacing t by \(\frac{1}{\lambda} (e^{\lambda t}-1 )\) in (28),

$$\begin{aligned}& \sum_{n=0} ^{\infty}\operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda)\frac {1}{n!} \biggl(\frac{1}{\lambda} \bigl(e^{\lambda t}-1 \bigr) \biggr)^{n} \\& \quad = \sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda )\frac{1}{n!} \lambda^{-n}n!\sum_{l=n} ^{\infty}S_{2}(l,n)\frac {(\lambda t)^{l}}{l!} \\& \quad =\sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n} \operatorname{Ch}_{m,q} ^{(h_{1},\ldots ,h_{r})}(x|\lambda)\lambda^{n-m}S_{2}(n,m) \Biggr) \frac{t^{n}}{n!} \end{aligned}$$
(32)

and, by (9),

$$\begin{aligned}& \prod_{i=1} ^{r} \biggl(\frac{q+1}{q^{h_{i}+1}(1+t)+1} \biggr) (1+t)^{x} \\& \quad = \Biggl(\prod_{i=1} ^{r-1} \Biggl( \sum_{n=0} ^{\infty}\operatorname{Ch}_{n,q} ^{(h_{i})}\frac{t^{n}}{n!} \Biggr) \Biggr) \Biggl(\sum _{n=0} ^{\infty }\operatorname{Ch}_{n,q} ^{(h_{r})}(x)\frac{t^{n}}{n!} \Biggr) \\& \quad = \sum_{n=0} ^{\infty}\sum _{\substack{l_{1}+\cdots+l_{r}=n \\l_{1},\ldots ,l_{r}\geq0}}\binom{n}{l_{1},\ldots,l_{r}}\operatorname{Ch}_{l_{1},q} ^{(h_{1})}\cdots \operatorname{Ch}_{l_{r-1},q} ^{(h_{r-1})} \operatorname{Ch}_{l_{r},q} ^{(h_{r})}(x)\frac{t^{n}}{n!}. \end{aligned}$$
(33)

Thus, by (32) and (33), we obtain the following theorem.

Theorem 3.2

For \(n\geq0\), we have

$$ \sum_{\substack{l_{1}+\cdots+l_{r}=n\\l_{1},\ldots,l_{r}\geq0}}\binom {n}{l_{1},\ldots,l_{r}}\operatorname{Ch}_{l_{1},q} ^{(h_{1})}\cdots \operatorname{Ch}_{l_{r-1},q} ^{(h_{r-1})} \operatorname{Ch}_{l_{r},q} ^{(h_{r})}(x)=\sum _{m=0} ^{n} \operatorname{Ch}_{m,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda)\lambda^{n-m}S_{2}(n,m). $$

q-Analog of higher order degenerate Changhee polynomials of the second kind

In this section, we consider the q-analog of higher order degenerate Changhee polynomials of the second kind is defined as follows:

$$\begin{aligned}& \widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) \\& \quad =\sum_{m=0} ^{n} \lambda^{n-m}S_{1}(n,m)\underbrace{{ \int_{\mathbb {Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}}_{r\text{-times}} q^{\sum_{i=1} ^{r}h_{i}y_{i}}(-x-y_{1} \\& \qquad {}- \cdots-y_{r})_{m}\,d\mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}), \end{aligned}$$
(34)

where n is a nonnegative integer. In particular, \(\widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots,h_{r})}(0|\lambda)=\widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots ,h_{r})}(\lambda)\) are called the q-analog of higher order degenerate Changhee numbers of the second kind.

By (7) and (34), it leads to

$$\begin{aligned}& \widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) \\& \quad = \sum_{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int_{\mathbb{Z}_{p}}}\cdots { \int_{\mathbb{Z}_{p}}}q^{\sum_{i=1} ^{r}h_{i}y_{i}}(-x-y_{1}-\cdots -y_{r})_{m}\,d\mu_{-q}(y_{1})\cdots \,d \mu_{-q}(y_{r}) \\& \quad = \sum_{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int_{\mathbb{Z}_{p}}}\cdots { \int_{\mathbb{Z}_{p}}}q^{\sum_{i=1} ^{r}h_{i}y_{i}}(-1)^{m} \\& \qquad {}\times (x+y_{1}+\cdots +y_{r})^{(m)}\,d \mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}) \\& \quad = \sum_{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int_{\mathbb{Z}_{p}}}\cdots { \int_{\mathbb{Z}_{p}}}q^{\sum_{i=1} ^{r}h_{i}y_{i}}(-1)^{m} \\& \qquad {}\times\sum _{l=0} ^{m}\bigl|S_{1}(m,l)\bigr|(x+y_{1}+ \cdots+y_{r})^{l} \,d\mu_{-q}(y_{1}) \cdots \,d\mu _{-q}(y_{r}) \\& \quad = \sum_{m=0} ^{n} \sum _{l=0} ^{m} \lambda^{n-m}S_{1}(n,m)\bigl|S_{1}(m,l)\bigr|(-1)^{m} \\& \qquad {} \times\sum_{\substack{l_{1}+\cdots+l_{r}=l\\l_{1},\ldots,l_{r}\geq 0}}\binom{l}{l_{1},\ldots,l_{r}}\prod _{i=1} ^{r-1}{ \int_{\mathbb {Z}_{p}}}q^{h_{i}y_{i}}y_{i} ^{l_{i}}\,d \mu_{-q}(y_{i}){ \int_{\mathbb {Z}_{p}}}q^{h_{r}y_{r}}(x+y_{r}) ^{l_{r}} \,d\mu_{-q}(y_{r}) \\& \quad = \sum_{m=0} ^{n} \sum _{l=0} ^{m} \sum_{\substack{l_{1}+\cdots+l_{r}=l \\l_{1},\ldots,l_{r}\geq0}} \binom{l}{l_{1},\ldots,l_{r}}\lambda ^{n-m}(-1)^{l} \\& \qquad {}\times S_{1}(n,m)S_{1}(m,l) \Biggl(\prod_{i=1} ^{r-1} E_{l_{i}} ^{(h_{i})}(q) \Biggr)E_{l_{r}} ^{(h_{r})}(x|q). \end{aligned}$$
(35)

Thus, we state the following theorem.

Theorem 4.1

For \(n \geq0\), we have

$$\begin{aligned} \widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) =&\sum _{m=0} ^{n} \sum _{l=0} ^{m} \sum_{\substack{l_{1}+\cdots+l_{r}=l\\l_{1},\ldots,l_{r}\geq 0}} \binom{l}{l_{1},\ldots,l_{r}}\lambda^{n-m}(-1)^{l}S_{1}(n,m)S_{1}(m,l) \\ &{}\times \Biggl(\prod_{i=1} ^{r-1} E_{l_{i}} (h_{i},q) \Biggr)E_{l_{r}} (x|h_{r},q). \end{aligned}$$

Now, we consider the generating function of the q-analog of higher order degenerate Changhee polynomials of the second kind as follows:

$$\begin{aligned}& \sum_{n=0} ^{\infty}\widehat{ \operatorname{Ch}}_{n,q} ^{(h_{1},\ldots ,h_{r})}(x|\lambda)\frac{t^{n}}{n!} \\& \quad = \sum_{n=0} ^{\infty} \sum _{m=0} ^{n} \lambda^{n-m}S_{1}(n,m){ \int _{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum_{i=1} ^{r} h_{i}y_{1}}(-x-y_{1} \\& \qquad {}- \cdots-y_{r})_{n}\,d\mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r})\frac {t^{n}}{n!} \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}}\sum_{n=0} ^{\infty}\binom{-x-y_{1}-\cdots -y_{r}}{n}\lambda^{-n}n! \\& \qquad {}\times\sum _{l=n} ^{\infty}S_{1}(l,n)\frac{(\lambda t)^{l}}{l!} \,d\mu_{-q}(y_{1})\cdots \,d\mu_{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}}\sum_{n=0} ^{\infty}\binom{-x-y_{1}-\cdots -y_{r}}{n} \\& \qquad {}\times\lambda^{-n} \bigl(\log(1+\lambda t) \bigr)^{n} \,d\mu _{-q}(y_{1})\cdots \,d \mu_{-q}(y_{r}) \\& \quad = { \int_{\mathbb{Z}_{p}}}\cdots{ \int_{\mathbb{Z}_{p}}}q^{\sum _{i=1} ^{r} h_{i}y_{i}} \biggl(1+\frac{1}{\lambda}\log(1+ \lambda t) \biggr)^{-x-y_{1}-\cdots-y_{r}}\,d\mu_{-q}(y_{1})\cdots \,d \mu_{-q}(y_{r}) \\& \quad = \prod_{i=1} ^{r} \biggl( \frac{1+q}{q^{h_{i}+1}+1+\frac{1}{\lambda}\log (1+\lambda t)} \biggr) \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{r-x}. \end{aligned}$$
(36)

In the special case \(r=1\),

$$ \sum_{n=0} ^{\infty} {\widehat{ \operatorname{Ch}}}_{n,h,q} (x|\lambda)\frac {t^{n}}{n!}= \frac{1+q}{q^{h+1}+1+\frac{1}{\lambda}\log(1+\lambda t)} \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{1-x}. $$
(37)

\({\widehat{\operatorname{Ch}}}_{n,q} ^{(h)}(x|\lambda)={\widehat {\operatorname{Ch}}}_{n,q}(x|h,\lambda)\) are called the q-analog of degenerate Changhee polynomials of the second kind.

By replacing t by \(\frac{1}{\lambda} (e^{\lambda t}-1 )\) in (36), we have

$$\begin{aligned} &\Biggl(\prod_{i=1} ^{r} \frac{[2]_{q}}{q^{h_{i}+1}+(1+t)} \Biggr) (1+t)^{r-x} \\ &\quad =\sum_{n=0} ^{\infty}\widehat{\operatorname{Ch}}_{n,q} ^{(h_{1},\ldots ,h_{r})}(x| \lambda)\frac{ (\frac{1}{\lambda}(e^{\lambda t}-1) )^{n}}{n!} \\ &\quad =\sum_{n=0} ^{\infty}\widehat{ \operatorname{Ch}}_{n,q} ^{(h_{1},\ldots ,h_{r})}(x|\lambda)\frac{1}{n!} \lambda^{-n}n!\sum_{l=n} ^{\infty} S_{2}(l,n)\frac{(\lambda t)^{l}}{l!} \\ &\quad =\sum_{n=0} ^{\infty} \Biggl(\sum _{m=0} ^{n} \widehat{\operatorname{Ch}}_{m,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda)\lambda^{n-m}S_{2}(n,m) \Biggr) \frac{t^{n}}{n!}, \end{aligned}$$
(38)

and, by (10), we get

$$\begin{aligned} & \Biggl(\prod_{i=1} ^{r} \frac{[2]_{q}}{q^{h_{i}+1}+(1+t)} \Biggr) (1+t)^{r-x} \\ &\quad = \Biggl(\prod_{i=1} ^{r-1} \Biggl( \sum_{n=0} ^{\infty} {\widehat { \operatorname{Ch}}}_{n,q} ^{(h_{i})}\frac{t^{n}}{n!} \Biggr) \Biggr) \Biggl(\sum_{n=0} ^{\infty} {\widehat{ \operatorname{Ch}}}_{n,q} ^{(h_{r})} (x)\frac{t^{n}}{n!} \Biggr) \\ &\quad =\sum_{n=0} ^{\infty} \biggl(\sum _{\substack{i_{1}+\cdots+i_{r}=n \\i_{1},\ldots,i_{r} \geq0}} \binom{n}{i_{1},\ldots,i_{r}}{\widehat { \operatorname{Ch}}}_{i_{1},q} ^{(h_{1})}\cdots{\widehat{ \operatorname{Ch}}}_{i_{r-1},q} ^{(h_{r-1})}{\widehat{\operatorname{Ch}}}_{i_{r},q} ^{(h_{r})}(x) \biggr)\frac{t^{n}}{n!}. \end{aligned}$$
(39)

By (38) and (39), we obtain the following theorem.

Theorem 4.2

For \(n \geq0\), we have

$$\begin{aligned}& \sum_{m=0} ^{n} \widehat{ \operatorname{Ch}}_{m,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda ) \lambda^{n-m}S_{2}(n,m) \\& \quad =\sum_{\substack{i_{1}+\cdots+i_{r}=n\\ i_{1},\ldots,i_{r} \geq0}} \binom {n}{i_{1},\ldots,i_{r}}{\widehat{ \operatorname{Ch}}}_{i_{1},q} ^{(h_{1})}\cdots{\widehat { \operatorname{Ch}}}_{i_{r-1},q} ^{(h_{r-1})}{\widehat{\operatorname{Ch}}}_{i_{r},q} ^{(h_{r})}(x). \end{aligned}$$

Note that

$$\begin{aligned}& \sum_{n=0} ^{\infty}{\widehat{ \operatorname{Ch}}}_{n,q} ^{(h_{1},\ldots ,h_{r})}(x|\lambda)\frac{t^{n}}{n!} \\& \quad = \prod_{i=1} ^{r} \biggl( \frac{1+q}{q^{h_{i}+1}+1+\frac{1}{\lambda}\log (1+\lambda t)} \biggr) \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{r-x} \\& \quad = \Biggl(\prod_{i=1} ^{r-1} \frac{(1+q)q^{-h_{i}-1}}{q^{-h_{i}-1} (1+\frac{1}{\lambda}\log(1+\lambda t) )+1} \Biggr) \biggl(1+\frac{1}{\lambda}\log(1+\lambda t) \biggr)^{r-1} \\& \qquad {} \times \biggl(\frac{(1+q)q^{-h_{r}-1}}{q^{-h_{r}-1} (1+\frac {1}{\lambda}\log(1+\lambda t) )+1} \biggr) \biggl(1+\frac {1}{\lambda} \log(1+\lambda t) \biggr)^{1-x} \\& \quad = \Biggl(\prod_{i=1} ^{r-1}q^{-h_{i}-1} \Biggr) \Biggl(\sum_{n=0} ^{\infty} \operatorname{Ch}_{n,q} ^{(-h_{1}-2,\ldots,-h_{r-1}-2)}(r-1|\lambda)\frac {t^{n}}{n!} \Biggr) \Biggl(\sum_{n=0} ^{\infty}{\widehat { \operatorname{Ch}}}_{n,-h_{r}-2,q}(x|\lambda)\frac{t^{n}}{n!} \Biggr) \\& \quad = \sum_{n=0} ^{\infty} \Biggl( \Biggl( \prod_{i=1} ^{r-1}q^{-h_{i}-1} \Biggr) \sum_{m=0} ^{\infty}\binom{n}{m} \operatorname{Ch}_{n-m,q} ^{(-h_{1}-2,\ldots,-h_{r-1}-2)}(r-1|\lambda){\widehat { \operatorname{Ch}}}_{m,-h_{r}-2,q}(x|\lambda) \Biggr)\frac{t^{n}}{n!}, \end{aligned}$$

and thus we see that

$$\begin{aligned}& {\widehat{\operatorname{Ch}}}_{n,q} ^{(h_{1},\ldots,h_{r})}(x|\lambda) \\& \quad = \Biggl(\prod_{i=1} ^{r-1}q^{-h_{i}-1} \Biggr)\sum_{m=0} ^{\infty }\binom{n}{m} \operatorname{Ch}_{n-m,q} ^{(-h_{1}-2,\ldots,-h_{r-1}-2)}(r-1|\lambda ){\widehat{ \operatorname{Ch}}}_{m,-h_{r}-2,q}(x|\lambda). \end{aligned}$$

Conclusion

The Changhee polynomials were defined by Kim, and have been attempted the various generalizations by many researchers (see [1, 6, 12, 13, 24,25,26, 28, 31]). The Changhee numbers (q-Changhee numbers, respectively) are closely relate with the Euler numbers (q-Euler numbers), the Stirling numbers of the first kind and second kind and the harmonic numbers, etc. which are interesting numbers of combinatorics, and pure and applied mathematics.

In this paper, we defined two types of the degenerate \((h,q)\)-Changhee polynomials and number, and found the relationship between the Stirling numbers of the first kind and second kind, \((h,q)\)-Euler numbers, q-Changhee numbers and those polynomials and numbers. It is a further problem to find the relationship between some special polynomials and degenerate \((h,q)\)-Changhee polynomials.

References

  1. Arici, S., Ağyüz, E., Acikgoz, M.: On a q-analogue of some numbers and polynomials. J. Inequal. Appl. 2015, 19 (2015)

    MATH  Article  Google Scholar 

  2. Bayad, A., Kim, T.: Identities involving values of Bernstein, q-Bernoulli, and q-Euler polynomials. Russ. J. Math. Phys. 18, 133–143 (2011)

    MathSciNet  MATH  Article  Google Scholar 

  3. Bóna, M.: Introduction to Enumerative and Analytic Combinatorics. CRC Press, Boca Raton (2016)

    Google Scholar 

  4. Carlitz, L.: Degenerate Stirling, Bernoulli and Eulerian numbers. Util. Math. 15, 51–88 (1979)

    MathSciNet  MATH  Google Scholar 

  5. Comtet, L.: Advanced Combinatorics. Reidel, Dordrecht (1974)

    MATH  Book  Google Scholar 

  6. Dolgy, D.V., Kim, T., Rim, S.H., Seo, J.J.: A note on Changhee polynomials and numbers with q-parameter. Int. J. Math. Anal. 8(26), 1255–1264 (2014)

    Article  Google Scholar 

  7. Gaboury, S., Tremblay, R., Fugere, B.-J.: Some explicit formulas for certain new classes of Bernoulli, Euler and Genocchi polynomials. Proc. Jangjeon Math. Soc. 17(1), 115–123 (2014)

    MathSciNet  MATH  Google Scholar 

  8. Kim, D.S., Kim, T.: Some symmetric identites for the higher-order q-Euler polynomials related to symmetry group \(S_{3}\) arising from p-adic q-fermionic integral on \(\mathbb{Z}_{p}\). Filomat 30(7), 1717–1721 (2016)

    MathSciNet  MATH  Google Scholar 

  9. Kim, D.S., Kim, T.: Some p-adic integrals on \({\mathbb{Z}}_{p}\) associated with trigonometric function. Russ. J. Math. Phys. 25(3), 300–308 (2018)

    MathSciNet  MATH  Google Scholar 

  10. Kim, D.S., Kim, T., Dolgy, D.V.: Degenerate poly-Cauchy polynomials with a q-parameter. J. Inequal. Appl. 2015, 364 (2015)

    MathSciNet  MATH  Article  Google Scholar 

  11. Kim, D.S., Kim, T., Jang, G.W.: A note on degenerate Stirling numbers of the first kind. Proc. Jangjeon Math. Soc. 21(3), 394–404 (2018)

    Google Scholar 

  12. Kim, D.S., Kim, T., Seo, J.J.: A note on Changhee polynomials and numbers. Adv. Stud. Theor. Phys. 7(20), 993–1003 (2013)

    Article  Google Scholar 

  13. Kim, D.S., Kim, T., Seo, J.J., Lee, S.H.: Higher-order Changhee numbers and polynomials. Adv. Stud. Theor. Phys. 8(8), 365–373 (2014)

    Article  Google Scholar 

  14. Kim, T.: On q-analogye of the p-adic log gamma functions and related integral. J. Number Theory 76(2), 320–329 (1999)

    MathSciNet  Article  Google Scholar 

  15. Kim, T.: q-Volkenborn integration. Russ. J. Math. Phys. 9(3), 288–299 (2002)

    MathSciNet  MATH  Google Scholar 

  16. Kim, T.: A new approach to q-zeta function. Adv. Stud. Contemp. Math. (Kyungshang) 11(2), 157–162 (2005)

    MathSciNet  MATH  Google Scholar 

  17. Kim, T.: q-Euler numbers and polynomials associated with p-adic q-integral. J. Nonlinear Math. Phys. 14(1), 15–27 (2007)

    MathSciNet  MATH  Article  Google Scholar 

  18. Kim, T.: An invariant p-adic q-integral on \({\mathbb{Z}}_{p}\). Appl. Math. Lett. 21(2), 105–108 (2008)

    MathSciNet  Google Scholar 

  19. Kim, T.: Some identities on the q-Euler polynomials of higher order and q-Stirling numbers by the fermionic p-adic integral on \(\mathbb{Z}_{p}\). Russ. J. Math. Phys. 16(4), 484–491 (2009)

    MathSciNet  MATH  Google Scholar 

  20. Kim, T.: A study on the q-Euler numbers and the fermionic q-integrals of the product of several type q-Bernstein polynomials on \({\mathbb{Z}}_{p}\). Adv. Stud. Contemp. Math. 23, 5–11 (2013)

    MATH  Google Scholar 

  21. Kim, T., Kim, D.S.: Identities for degenerate Bernoulli polynomials and Korobov polynomials of thd first kind. Sci. China Math. (2017). https://doi.org/10.1007/s11425-018-9338-5

    Article  Google Scholar 

  22. Kim, T., Kim, D.S.: Degenerate Laplace transform and degenerate gamma function. Russ. J. Math. Phys. 24(2), 241–248 (2017)

    MathSciNet  MATH  Article  Google Scholar 

  23. Kim, T., Kim, D.S., Dolgy, D.V.: Degenerate q-Euler polynomials. Adv. Differ. Equ. 2015, 13662 (2015)

    MathSciNet  MATH  Google Scholar 

  24. Kim, T., Kwon, H.I., Seo, J.J.: Degenerate q-Changhee polynomials. J. Nonlinear Sci. Appl. 9, 2389–2393 (2016)

    MathSciNet  MATH  Article  Google Scholar 

  25. Kim, T., Mansour, T., Rim, S.H., Seo, J.J.: A note on q-Changhee polynomials and numbers. Adv. Stud. Theor. Phys. 8(1), 35–41 (2014)

    Article  Google Scholar 

  26. Kwon, H.I., Kim, T., Seo, J.J.: A note on degenerate Changhee numbers and polynomials. Proc. Jangjeon Math. Soc. 18(3), 295–305 (2015)

    MathSciNet  MATH  Google Scholar 

  27. Milovanović, G.V., Rassias, M.T.: Analytic Number Theory, Approximation Theory, and Special Functions. Springer, New York (2014)

    MATH  Book  Google Scholar 

  28. Moon, E.-J., Park, J.W.: A note on the generalized q-Changhee numbers of higher order. J. Comput. Anal. Appl. 20(3), 470–479 (2016)

    MathSciNet  MATH  Google Scholar 

  29. Ozden, H., Simsek, Y.: A new extension of q-Euler numbers and polynomials related to their interpolation functions. Appl. Math. Lett. 21(9), 934–939 (2008)

    MathSciNet  MATH  Article  Google Scholar 

  30. Ozden, H., Simsek, Y., Cangul, I.N.: Euler polynomials associated with p-adic q-Euler measure. Gen. Math. 15(2), 24–37 (2007)

    MathSciNet  MATH  Google Scholar 

  31. Park, J.W., Kwon, J.: A note on the \((h,q)\)-Changhee numbers and polynomials (submitted)

  32. Ryoo, C.S.: The structure of the roots of \((h,q)\)-Euler polynomials. Far East J. Math. Sci. 48, 131–138 (2011)

    MathSciNet  MATH  Google Scholar 

  33. Sharma, A.: q-Bernoulli and Euler numbers of higher order. Duke Math. J. 25, 343–353 (1958)

    MathSciNet  MATH  Article  Google Scholar 

  34. Simsek, Y.: Twisted \((h,q)\)-Bernoulli numbers and polynomials related to twisted \((h,q)\)-zeta function and L-function. J. Math. Anal. Appl. 324(2), 790–804 (2006)

    MathSciNet  MATH  Google Scholar 

  35. Simsek, Y.: Complete sum of products of \((h,q)\)-extension of Euler polynomials and numbers. J. Differ. Equ. Appl. 16(11), 1331–1348 (2010)

    MathSciNet  MATH  Google Scholar 

  36. Srivastava, H.: Some generalizations and basic (or q-)extensions of the Bernoulli, Euler and Genocchi polynomials. Appl. Math. Inf. Sci. 5, 390–444 (2011)

    MathSciNet  Google Scholar 

  37. Zhang, Z., Yang, H.: Some closed formulas for generalized Bernoulli–Euler numbers and polynomials. Proc. Jangjeon Math. Soc. 11(2), 191–198 (2008)

    MathSciNet  MATH  Google Scholar 

Download references

Acknowledgements

The authors would like to thank the referees for their valuable and detailed comments which have significantly improved the presentation of this paper.

Funding

This research was supported by the Daegu University Research Grant, 2018.

Author information

Authors and Affiliations

Authors

Contributions

All authors contributed equally to this work. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Jin-Woo Park.

Ethics declarations

Competing interests

The authors declare that they have no competing interests.

Additional information

Publisher’s Note

Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Rights and permissions

Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Kim, Y., Park, JW. On the degenerate \((h,q)\)-Changhee numbers and polynomials. J Inequal Appl 2019, 5 (2019). https://doi.org/10.1186/s13660-019-1957-2

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/s13660-019-1957-2

Keywords

  • \((h,q)\)-Euler polynomials
  • Degenerate \((h,q)\)-Changhee polynomials
  • Fermionic p-adic q-integral on \({\mathbb{Z}}_{p}\)